Prescribing Practices of Intravenous Immunoglobulin in Tertiary Care Hospitals in Malaysia: A Need for a National Guideline for Immunoglobulin Use - Lee, Jian Lynn; Mohd Saffian, Shamin; Makmor-Bakry, Mohd; Islahudin, Farida; Alias, Hamidah; Ali, Adli; Mohamed Shah, Noraida (Frontiers in Pharmacology, 2022)
Rational use of drug involves the use of medicine as per clinical guidelines. Given the steady increase in the clinical utility of intravenous immunoglobulin (IVIG) either as licensed or off-label use, concerns are being raised about the possibility of supply shortages that could significantly impact patient care. Therefore, there is a need to regulate and to promote the rational use of this valuable medication. This cross-sectional chart review study attempts to evaluate the prescribing patterns of IVIG at two tertiary hospitals in Malaysia. Patients' medical files and dispensing records were examined and compared with current guidelines. A total of 348 prescriptions for IVIG were written during the 1-year study period. The highest usage of IVIG was for neurological (47.9%), immunological (27.5%), and hematological conditions (20%). The number of prescriptions with the US Food and Drug Administration (FDA) licensed indications and off-label indications was 148 (42.5%) and 200 (57.5%), respectively. Age (OR: 1.02, 95% CI: 1.01 – 1.03, p = 0.003) and those admitted to the critical care units (OR: 11.11, 95% CI: 5.60 – 22.05, p < 0.001) were significant factors for receiving IVIG for an off-label indication. Most prescriptions (79%) had appropriate dosing. Significant factors associated with receiving inappropriate dose of IVIG include age (OR: 0.93, 95% CI: 0.89 – 0.97, p = 0.001) and those admitted to the critical care units (OR: 10.15, 95% CI: 3.81 – 27.06, p < 0.001). This study advocates the development and implementation of evidence-based clinical guidelines with prioritization protocol to ensure rational use of IVIG.